Eight-Year Trend Analysis of Cutaneous Leishmaniasis Cases in West Amhara Region Referred to Amhara Public Health Institute Northwest, Ethiopia: A Retrospective Study. (22nd August 2022) - Tegegne, Banchamlak; Yimer, Mulat; Ejigu, Kefale; Alemu, Getaneh; Estifanos, Fikirte
Abstract : Cutaneous leishmaniasis is a continually spreading health problem in Amhara Region, Ethiopia. Despite this, up- to-date information on referral laboratory facility has been not yet reported. Therefore, this study was aimed at reporting up-to-date information about eight year's cutaneous leishmaniasis trend status. Data on referred cases from 2013 to 2020 were collected at Amhara Public Health Institute Parasitology department by reviewing log book. Of the 243 suspected cases, 114 (46.9%) were positive (confirmed) with microscope and cultured results showed that most of them were negatives. Most of the suspected cases were from 16 to 30 years and males by age and sex, respectively. Trend status by year depicted that largest numbers of suspected and confirmed cases were reported in 2013, 2015, and 2019 years. Finally, the trend status by zone showed that most cases were reported from South Gondar and Awi zones, respectively.